Reducing time in acute hospitals: A stepped-wedge randomised control trial of a specialist palliative care intervention in residential care homes. (May 2020) - Forbat, Liz; Liu, Wai-Man; Koerner, Jane; Lam, Lawrence; Samara, Juliane; Chapman, Michael; Johnston, Nikki
Background: Care home residents are frequently transferred to hospital, rather than provided with appropriate and timely specialist care in the care home. Aim: To determine whether a model of care providing specialist palliative care in care homes, called Specialist Palliative Care Needs Rounds, could reduce length of stay in hospital. Design: Stepped-wedge randomised control trial. The primary outcome was length of stay in acute care (over 24-h duration), with secondary outcomes being the number and cost of hospitalisations. Care homes were randomly assigned to cross over from control to intervention using a random number generator; masking was not possible due to the nature of the intervention. Analyses were by intention to treat. The trial was registered with ANZCTR: ACTRN12617000080325. Data were collected between 1 February 2017 and 30 June 2018. Setting/participants: 1700 residents in 12 Australian care homes for older people. Results: Specialist Palliative Care Needs Rounds led to reduced length of stay in hospital (unadjusted difference: 0.5 days; adjusted difference: 0.22 days with 95% confidence interval: −0.44, −0.01 and p = 0.038). The intervention also provided a clinically significant reduction in the number of hospitalisations by 23%, from 5.6 to 4.3 per facility-month. A conservative estimate of annual net cost-saving from reduced admissions was A1, 759, 011 (US1.3 m; UK£0.98 m). Conclusion: The model of care significantly reduces hospitalisations through provision of outreach by specialist palliative care clinicians. The data offer substantial evidence for Specialist Palliative Care Needs Rounds to reduce hospitalisations in older people approaching end of life, living in care homes.